La “otra” Independencia de México: el primer imperio mexicano. Claves para la reflexión histórica - Frasquet, Ivana (Revista Complutense de Historia de América, 2008)
The independence of Mexico has been studied from many different subjects and historiographical points of view. In this paper we intend to revise some works, which from political change have contributed to understand the independent process, as soon the classic historiography about Iturbide. This will help to understand, from wider views, a process that cannot be studied from historical personalisms.